A study of high-performance slag-based composite admixtures. (30th November 2017) - Li, Zaibo; Zhao, Xuguang; He, Tusheng; Zhao, Sanyin; Liu, Yang; Qu, Xiaoling
Highlights: The SCAs consist of granulated blast furnace slag, steel slag, fly ash and boundary limestone. The effects of the composition of the SCAs on the shrinkage, stability and bleeding capacity of the mortar. The relationships between the raw material composition, performance and structure of the high-performance SCAs. The exceptional performance of SCAs results from the advantageous synergistic effects of GGBFS and SS. Abstract: To promote the large-scale application of ground granulated blast furnace slag powder (GGBFS) in the cement and concrete industry, high-performance slag-based composite admixtures (SCAs) were prepared with GGBFS as the main raw material and converter steel slag powder (SS), limestone powder (LP) and fly ash (FA) as auxiliary raw materials. The effects of the fineness and content of each auxiliary raw material on the performance of the SCA were investigated. The experimental results showed that SS had multiple beneficial effects on mortar and concrete; it can increase the strength, reduce the bleeding and compensate for the shrinkage of the concrete. The best performance of medium- and low-strength concrete with a high SCA content was achieved using the SCA with the following composition: GGBFS: 64%; SS: 20%; LP: 6%; and FA: 10%. The fresh Portland cement (PC) + SCA concrete specimens had better fluidity and stability than the PC + GGBFS concrete specimen, and the compressive strengths of the PC + SCA concrete specimens were the same or slightly higher than that of the PC + GGBFS concrete specimen. The results of scanning electron microscopy, X-ray photoelectron spectroscopy and pore size analysis showed that the concrete specimens prepared with PC + SCA had significantly smaller and fewer large pores and a more uniform and dense interfacial structure than the concrete specimen prepared with PC + GGBFS. The exceptional performance of SCAs results from the advantageous synergistic effects of GGBFS and SS.